Self-mentions in design area disciplines: A corpus analysis - Victor(ia) Batres-Prieto; Asad Abbas (Heliyon)
This study analyzes the self-mention forms represented by first-person pronouns (I, me, my, we, us, and our), self-citations, and other forms of mentions made by the same author(s) in each article (e.g., this writer, the author, the authors, the research team) in a corpus of academic articles (625,195 words) in Design area disciplines to determine the similarities and differences in self-mention practices within these disciplines and the previous findings reported in the literature of authorial self-representation observed in hard and soft fields. A quantitative approach using the method employed by Hyland in 2001 [23] explored a corpus of 100 academic empirical and theoretical articles on visual arts, design, architecture, and art and design education (25 for each discipline) obtained from Q1 and Q2 journals listed in the Visual Arts and Performing Arts subject area of Scopus. The results suggest that self-mention practices in Design area disciplines share similarities and differences with the authorial self-representation in soft and hard fields previously reported in the literature by Hyland in 2001 [23] and Dixon in 2022 [24]. Overall, self-mentions in Design area disciplines resemble the authorial self-representation practices in soft fields. However, self-mentions in architecture tend to use the impersonal writing of hard fields because this discipline has a close historical relationship with engineering. This is the first corpus analysis of self-mention practices in academic articles in the Design area disciplines. The implications of the findings for academic literacy are also discussed.